Chemical composition, antibacterial activity of Cyperus rotundus rhizomes essential oil against Staphylococcus aureus via membrane disruption and apoptosis pathway. (October 2017) - Zhang, Liang-Liang; Zhang, Li-Fang; Hu, Qing-Ping; Hao, Dong-Lin; Xu, Jian-Guo
Abstract: The chemical composition, antibacterial activity and mechanism of essential oil from Cyperus rotundus rhizomes against Staphylococcus aureus were investigated in this study. Results showed that α-cyperone, cyperene and α-selinene were the major components of the essential oil. The essential oil exhibited strong antibacterial activity against S. aureus with the minimum inhibitory concentration (MIC) and minimum bactericide concentration (MBC) were 10 and 20 mg/mL respectively, and the antibacterial effects increased with increasing essential oil concentrations and treatment time. The electric conductivity, cell membrane integrity, NPN uptake, and membrane potential assays demonstrated that essential oil disrupted the membrane integrity of S. aureus . Electron microscope observations further confirmed that essential oil destroyed cell membrane. Moreover, we found that essential oil could induce cells death of S. aureus through apoptosis pathway based on apoptosis analysis. These findings suggested that essential oil mainly exerted antibacterial activity by damaging cell membrane and membrane-mediated apoptosis pathway. Highlights: Analyzed the chemical compositions of Cyperus rotundus rhizomes essential oil. Investigated the antibacterial properties of essential oil against Staphylococcus aureus. Evaluated the action mechanism of essential oil against Staphylococcus aureus.